Analysis of Dislocations in PVT-Grown 6H-SiC through Grazing-Incidence X-Ray Topographic Images and Ray-Tracing Simulation. (8th September 2020) - Cheng, Qianyu; Ailihumaer, Tuerxun; Peng, Hongyu; Liu, Yafei; Raghothamachar, Balaji; Dudley, Michael
Abstract : The superior electronic and physical properties of silicon carbide (SiC) enabled successful applications in electronic and optoelectronic applications. Therefore, understanding the nature and behavior of different dislocations is of great significance towards crystal quality enhancement and device degradation prevention. In this study, synchrotron monochromatic beam X-ray topography (SMBXT) analysis was carried out on a PVT-grown 6H-SiC wafer for recording its grazing-incidence images of all six different 1 1 2‾12 reflections. The distribution of TSDs, TEDs, TMDs and BPDs has been observed on topographic images, and characterized through correlation with ray-tracing simulation. The conjunction of topographic and simulated images in this study has successfully accomplished a direct Burgers vectors determination approach for each type of dislocations, which can provide crucial information for quality improvement of crystal.